2011
DOI: 10.1140/epjd/e2011-20194-0
|View full text |Cite
|
Sign up to set email alerts
|

Emission spectra and intrinsic optical bistability in a two-level medium

Abstract: Abstract. Scattering of resonant radiation in a dense two-level medium is studied theoretically with account for local field effects and renormalization of the resonance frequency. Intrinsic optical bistability is viewed as switching between different spectral patterns of fluorescent light controlled by the incident field strength. Response spectra are calculated analytically for the entire hysteresis loop of atomic excitation. The equations to describe the non-linear interaction of an atomic ensemble with lig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
(72 reference statements)
1
6
0
2
Order By: Relevance
“…Using this chain, we manage to obtain the expression for the local field acting on the atom self-consistently from the initial Hamiltonian. The included terms also affect the optical properties of the system, such as the radiation and absorption spectra [17], but considering the last problem is beyond the scope of this paper.…”
Section: Bbgky Hierarchymentioning
confidence: 99%
“…Using this chain, we manage to obtain the expression for the local field acting on the atom self-consistently from the initial Hamiltonian. The included terms also affect the optical properties of the system, such as the radiation and absorption spectra [17], but considering the last problem is beyond the scope of this paper.…”
Section: Bbgky Hierarchymentioning
confidence: 99%
“…Из этой новой цепочки нам удалось самосогласованно получить выражение для локального поля, действующего на атом, из начального гамильтониана. Учтенные слагаемые также будут влиять и на оптические свойства системы такие, как спектр излучения и спектр поглощения [17], однако рассмотрение последнего вопроса выходит за рамки настоящей статьи.…”
Section: гамильтониан гамильтониан рассматриваемой системы в предстаunclassified
“…In this report we propose a theoretical explanation based on the possibility for a cooperative ensemble of emitting centres to show intrinsic cooperative optical multistability [4]. It is shown that the Maxwell-Bloch type equations describing such a system [5], even in the presence of large values of the phase relaxation rate, retain the possibility of having several stable steady state solutions that form a multistable optical response for certain combinations of the pump power and concentration of the emitters. A numerical analysis has shown that the transition time may exceed the lifetime by an order of magnitude.…”
mentioning
confidence: 97%